The use of mean platelet volume for distinguishing the causes of thrombocytopenia in adult patients - Lalita Norrasethada (2019)
© L. Norrasethada et al. Establishment and analysis of mean platelet volume (MPV) may be helpful in the discrimination between underproduc-tion or over-destruction of platelets as the causes of thrombocytopenia. The primary objective is to find the cut-off point of MPV for distinguishing causes of thrombocytopenia. The secondary objective is to validate the cut-off value of the MPV by using bone marrow examination. Thrombocytopenic patients were enrolled in a training set and a receiving operating characteristics (ROC) curve was plotted to obtain the cut-off value of MPV. A validation set of patients was recruited to validate the cut-off value. The training set included 240 patients. Half with with underproductive (n=120) and half with over-destructive thrombocytopenia (n=120). The best cut-off value of MPV was 8.8 fL. The validation set included 119 patients in total, again in 2 groups, those with underproductive (n=84) and those with over-destructive thrombocytopenia (n=35). The sensitivity, specificity, PPV and NPV when MPV ≥8.8 fL indicating over-destructive thrombocytopenia were 77%, 89%, 89% and 77%, respectively. MPV is useful for differentiating the cause of thrombocytopenia. The value of MPV ≥8.8 fL has acceptable sensitivity and specificity for diagnosis of over-destructive thrombocytopenia.